2023
DOI: 10.1029/2022jg007107
|View full text |Cite
|
Sign up to set email alerts
|

Shrubs Compensate for Tree Leaf Area Variation and Influence Vegetation Indices in Post‐Fire Siberian Larch Forests

Abstract: A large and growing body of research suggests that the magnitude of warming due to anthropogenic climate change in the Arctic is four times the global average (Previdi et al., 2021;Rantanen et al., 2022;Serreze & Barry, 2011). This Arctic amplification is partly due to sea ice loss across the Arctic, which decreases regional albedo and amplifies warming, a process known as the sea ice-albedo feedback (Hudson, 2011;Perovich & Polashenski, 2012;Previdi et al., 2021; Winton, 2006). The extreme magnitude of this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 102 publications
(170 reference statements)
0
6
0
Order By: Relevance
“…For example, 90% of open evergreen tree samples had an understory of deciduous shrubs, increasing the greenness of open evergreen trees relative to closed evergreen trees. Similarly, other studies have shown that forest greenness is positively correlated with understory shrub cover, while weakly or negatively correlated with overstory conifer cover due to masking understory shrubs (Loranty et al, 2018;Bendavid et al, 2023).…”
Section: Open Vs Closed Canopy Pftsmentioning
confidence: 62%
See 1 more Smart Citation
“…For example, 90% of open evergreen tree samples had an understory of deciduous shrubs, increasing the greenness of open evergreen trees relative to closed evergreen trees. Similarly, other studies have shown that forest greenness is positively correlated with understory shrub cover, while weakly or negatively correlated with overstory conifer cover due to masking understory shrubs (Loranty et al, 2018;Bendavid et al, 2023).…”
Section: Open Vs Closed Canopy Pftsmentioning
confidence: 62%
“…Greenness has also been shown to vary with plant composition (Boelman et al, 2011; Anderson et al, 2016; Bendavid et al, 2023). For example, deciduous shrubs are generally “greener” than other plant functional types (PFTs), such as graminoids (Raynolds et al, 2008; Berner et al, 2018; Jespersen et al, 2023), thus suggesting that Arctic greening is partially driven by deciduous shrub expansion (Forbes et al, 2010; Myers-Smith et al, 2011; Fraser et al, 2014; Frost et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study detailing a transect in eastern Canada from boreal to high-Arctic latitudes found that shrubs were a primary determinant of snow thermal conductivity via impacts on depth hoar formation (Royer et al 2021). One possible explanation for the winter soil temperature patterns we observed is that greater shrub abundance in low density stands at our study site (Paulson et al 2021, Bendavid et al 2023 could facilitate depth hoar formation.…”
Section: Why Are Soils Colder Under Dense Larch Canopies In Winter?mentioning
confidence: 81%
“…In this study, we used data collected from six study sites situated across a gradient of forest cover in northeastern Siberia to quantify variation in winter soil temperature dynamics in relation to canopy cover. Canopy cover at the sites ranges from 13% to >70%; permafrost active layer depth and understory tall shrub cover decrease with increasing canopy cover, while understory moss cover increases with canopy cover (Paulson et al 2021, Bendavid et al 2023. Data were collected over seven years, during which there was considerable variation in snow accumulation, allowing us to investigate the influence of snow cover variation on winter soil temperature as well.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy between field and remote sensing‐based estimates of vegetation destruction could be due to limitations of field‐based research that only allow us to sample a small proportion of all fires, whereas remote sensing analyses can be employed at the biome‐scale. Alternatively, differences between field and remote sensing‐based estimates could reflect the poor performance of standard remote sensing products in larch ecosystems (Bendavid et al., 2023; Loranty et al., 2018; Montesano et al., 2016), particularly in regions with low canopy cover (Montesano et al., 2009). Accordingly, we found no relationship between the site mean dNBR and the percentage of the aboveground C pool combusted ( p = 0.2).…”
Section: Resultsmentioning
confidence: 99%